The Examination of Persuasion and Convenience Methods in the Holy Quran about the Issue of the Last Day (Qiyāmah) - Sahar Musalla Nezhad; Muhammad Hadi Fallahi; Behzad Moridi (آموزه‌های قرآنی, 2021)
Allah almighty for persuading addressees and proving legitimacy and rightfulness of His sayings has utilized different persuasive methods. The process of persuasion is one of the most functioning matters of discourse analysis. This process is used to control the addressees’ minds and to convey the message. The present paper examines the persuasive methods and how to be applied them to encourage the addressees in al-Qiyamah, al-Waqiah, al-Ghashiyah, an-Naba and Abasa surahs (Arabic: سُوَر القیامة، الواقعة، الغاشیة، النبأ، عبس) that they are all just about the subject of the day of judgment (Qiyamah). With using the Hovland model and verisimilitude model of the cognitive exegesis it is studied the persuasive components. In this note it has been used the Quran translation which has been produced by ayatollah Makarem Shirazi and also Almizan and Noor exegeses. With applying descriptive-integrated method the results shows that all parts of the models have been used in each of surahs. According to the Hovland model these surahs have many arguments, fear, threat, questioning and answering in comparison to other persuasive cases. For presenting many arguments in all mentioned surahs, it is cleared that the central method which emphasizes the argumentative content has used more and this indicates an approach based on the Quran thought in persuading addressees.